The Teachers’ Strategies in Teaching English Vocabulary: An Analysis of Teachers’ in Youtube: Abdul Khaliq - Abdul Khaliq (Samudra Publisher, 2023)
The research aimed to analyze the teachers’ strategy in teaching English vocabulary conducted by teachers to students on Youtube Video. It is conducted to know how the Teachers strategy is implemented by the teacher such as the material that the teacher used, the media that the teacher used, and the strategies that the teacher used. The researcher used descriptive qualitative to analyze the data. The researcher collected the data by observing Teachers’ strategies in teaching vocabulary on Video Youtube and analyzing teachers’ strategies in teaching English vocabulary on video youtube. The object of this research focuses on the teachers’ strategies in teaching English vocabulary in a case video on youtube. Based on the collecting of the data, the researcher concluded that the material used by the English teacher is the Jobs such as (1) Astronaut, (2) Shop assistant, Etc. The media used by English teachers were pictures. Then, the strategies used by the teacher were: presentation, practicing, and explaining